2021
DOI: 10.1111/os.12795
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Ultrasound‐Guided Iliohypogastric/Ilioinguinal Nerve Block Combined with Lateral Femoral Cutaneous Nerve Block in Total Hip Arthroplasty via Direct Anterior Approach: A Retrospective Cohort Study

Abstract: Objective This study aimed to explore the efficacy and safety of the combination of lateral femoral cutaneous nerve blocks (LFCNB) and iliohypogastric/ilioinguinal nerve blocks (IHINB) on postoperative pain and functional outcomes after total hip arthroplasty (THA) via the direct anterior approach (DAA). Methods In this retrospective cohort study, patients undergoing THA via the DAA between January 2019 and November 2019 were stratified into two groups based on their date of admission. Sixty‐seven patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“… 23 Wang et al measured the effect of lateral femoral cutaneous nerve and iliohypogastric/ilioinguinal nerve blocks on postoperative quality of recovery at 24 and 48 h after THA; however, the clinical significance was observed only at 24 h postoperatively. 24 In our study, CFICB improved the quality of recovery only at 24 h after THA; however, it was surprising that we used continuous regional block to provide postoperative analgesia for patients, while Wang et al used only a single injection regional block. Therefore, which regional analgesic technique could significantly improve the postoperative quality of recovery for THA needs to be determined.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 23 Wang et al measured the effect of lateral femoral cutaneous nerve and iliohypogastric/ilioinguinal nerve blocks on postoperative quality of recovery at 24 and 48 h after THA; however, the clinical significance was observed only at 24 h postoperatively. 24 In our study, CFICB improved the quality of recovery only at 24 h after THA; however, it was surprising that we used continuous regional block to provide postoperative analgesia for patients, while Wang et al used only a single injection regional block. Therefore, which regional analgesic technique could significantly improve the postoperative quality of recovery for THA needs to be determined.…”
Section: Discussionmentioning
confidence: 58%
“…Some studies have investigated the influence of other regional blocks on the quality of recovery after THA using the QoR-15 score. [23][24][25] Lennon et al assessed the effect of the erector spinae plane block on the quality of recovery at 24 h after THA, and the results showed that the erector spinae plane block did not improve postoperative quality of recovery in THA. 23 Wang et al measured the effect of lateral femoral cutaneous nerve and iliohypogastric/ilioinguinal nerve blocks on postoperative quality of recovery at 24 and 48 h THA; however, the clinical significance was observed only at 24 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies were excluded for a lack of comparison arm, irrelevance, not the bikini incision, or full texts unavailable, leaving 8 comparative studies eligible for final inclusion in this qualitative review ( Fig. 2 ) [ 9 , 12 , [16] , [17] , [18] , [19] , [20] , [21] ].
Figure 2 Preferred Reporting Items for Systematic Review and Meta-Analyses flow diagram.
…”
Section: Resultsmentioning
confidence: 99%
“…The included studies reported a total of 2313 patients that underwent DAA THA using a bikini (n = 952) vs longitudinal incision (n = 1361). Seven studies reported mean age and sex proportion; in the bikini incision group, mean patient age ranged from 54.3 [ 20 ] to 70 [ 12 ] years, and the majority of reported patients were female (550/952; 57.8%). In the longitudinal incision group, the mean patient age ranged from 55 [ 20 ] to 67.4 [ 18 ] years, and the majority of reported patients were female (620/1132; 54.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation